COMPARATIVE PERFORMANCE ANALYSIS OF SOLAR STILL WITH AND WITHOUT BASIN LINE WITH BLACK POLYTHENE FILM - Musa, Nicholas Akhaze; Igoh, Hassan Ibrahim (FUDMA JOURNAL OF SCIENCES, 2024)
Since a solar still's optimal performance is crucial, improvements to both its component designs and environmental factors have received attention. Thus, the focus of this study was the solar still basin. First, a black polythene film was used to line the basin of a planned solar still. The yield of this method was assessed, and then the black polythene film was taken out of the basin and another assessment was made. Hourly measurements of the ambient, glass, basin, and solar intensity as well as the distilled water were made in each case.  The experiments' results showed that the temperature of the environment, the glass, and the water in the solar still's basin all increased in tandem with the sun's intensity.   The solar still's production rose by 9.1 % per day on average when 0.15 mm black polythene film was used to line the basin. The study confirms that using black polythene film into solar still designs provides a workable and effective way to increase potable water production rates.
Keywords: Solar still; Glass cover; Water depth; Basin; Yield